Ekspresi fenotipe gen APETALA1 kakao (TcAP1) pada eksplan tembakau Phenotypic expression of cacao APETALA1 (TcAP1) in tobacco explant - Tetty CHAIDAMSARI; . SAMANHUDI; Asmini BUDIANI; Roedhy POERWANTO; Djoko SANTOSO (Menara Perkebunan, 2006)
Summary APETALA1 (AP1) is one of flowering identity genes that determines the formation of sepal and petal tissues. An AP1 homologue was cloned from cacao flowers by bio-techniques coupled with bio-informatics. Examination of phenotypic expression was conducted with transgenesis of the 35S-TcAP1 construct using leaf disk technique of tobacco leaf explants mediated by Agrobacterium tumefaciens. PCR specific to TcAP1 demonstrated that the technique is effective in introducing the 35S-TcAP1 construct into tobacco plant cells. RT-PCR with total RNA from the leaves of transgenic tobacco plantlets showed that expression levels of the TcAP1 events varied. The variation of the transcript levels was comparable to the morphological phenotype of the tobacco plantlets grown in vitro. The cultures expressing TcAP1 at moderate levels, have developed into intact plantlets and set up flowers in vitro.Ringkasan APETALA1 (AP1) diketahui merupakan salah satu gen identitas pembungaan yang mengendalikan terbentuknya jaringan sepal dan petal. Homolog AP1 telah diklon dari organ bunga kakao (TcAP1) dengan kombinasi bio-techniques dan bio-informatics. Pengujian ekspresi fenotipe TcAP1 dilakukan dengan transgenesis konstruk konstitutif 35S-TcAP1 menggunakan teknik leaf disk eksplan daun tembakau dan mediasi Agrobacterium tumefaciens. Pengujian PCR spesifik TcAP1 menunjukkan bahwa teknik tersebut cukup efektif dalam mengintroduksikan konstruk 35S-TcAP1 ke dalam sel tanaman tembakau. RT-PCR dari daun planlet tembakau trangenik membuktikan bahwa tingkat ekspresi TcAP1 tersebut bervariasi. Perbedaan level ekspresi TcAP1 ini memberikan pengaruh yang nampak sebanding terhadap perkembangan morfologis planlet tembakau in vitro.  Kultur yang mengekspresikan TcAP1 pada level sedang mampu beregenerasi menjadi planlet sempurna dan membentuk bunga in vitro.